The Reggio Emilia Approach to Early Childhood Education: An Introduction - Julian Liunardi (ANIMA Indonesian Psychological Journal, 2014)
In the last decade, the Indonesian government has become more aware of the importance of the development and education of the early years of children’s lives. Long before Indonesia started its journey in providing quality Early Childhood Education (ECE) for all young children, the people of Reggio Emilia city had developed sound practice in ECE that was well-known all over the world for its quality. This paper presented a literature review and described the Reggio Emilia Approach to ECE. Several suggestions as to how to adapt this approach in Indonesia’s early childhood services were also discussed. Dalam dekade terakhir, pemerintah Indonesia makin menyadari akan pentingnya pendidikan pada tahun-tahun awal kehidupan anak-anak. Jauh sebelum Indonesia memulai perjalanannya dalam memberikan Pendidikan Anak Usia Dini (PAUD) yang berkualitas untuk semua anak- anak, penduduk kota Reggio Emilia telah mengembangkan praktek PAUD yang terkenal berkualitas di seluruh dunia. Makalah ini menyajikan tinjauan literatur dan mendeskripsikan pendekatan PAUD Reggio Emilia. Beberapa saran mengenai bagaimana menyesuaikan pendekatan ini di Indonesia juga dibahas.